Fentanyl versus nalbuphine for intubating conditions during awake fiberoptic bronchoscopy: A randomized double-blind comparative study - Sujata Chaudhary; Sachin Chaudhary; Mahendra Kumar; Rashmi Salhotra (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Patient cooperation, sedation, anxiolysis, and topicalization are important prerequisites for the successful and safe conduct of awake intubation. Because of the pharmacological properties, opioids can facilitate this process. Fentanyl is an opioid agonist and nalbuphine is an agonist-antagonist. This study aims to compare these two opioids for their effect on sedation and intubating conditions during awake fiberoptic intubation. Material and Methods: This randomized double-blind controlled study was conducted on 62 ASA I/II patients of either sex between the age of 20 and 60 years, weight between 40 and 80 kg, with MP class I/II airways requiring general anesthesia with endotracheal intubation. All patients received standard airway topicalization and nebulization. Patients were randomly allocated to one of the two groups according to a computer-generated random number table. Group F (n = 31) received fentanyl 2 μg/kg i.v. and group N (n = 31) received nalbuphine 0.2 mg/kg i.v. over 10 min before intubation. Fiberoptic intubation was attempted and lignocaine spray and propofol boluses were administered as and when required. Hemodynamic responses and intubating conditions were recorded. Repeated measure ANOVA, McNemar test, and Chi-square test or Fischer's exact test were used for data analysis. A P < 0.05 was considered significant. Results: Cough score (P = 0.458), post-intubation score (P = 1.000), and sedation score (P = 1.000) were comparable among the two groups. Hemodynamic responses and propofol and lignocaine requirements were also comparable. Conclusion: Both fentanyl and nalbuphine provide comparable intubating conditions when used before awake fiberoptic intubation with minimal adverse effects on hemodynamic profile.